Implementation of Halal Label Recognition on Everyday Snacks for Early Childhood Children - Milza, Milza; Sameto, Mayang Belia; Handayani, Sisi Sri; Ardilla, Rima; Yanti, Tri (Ahlussunnah: Journal of Islamic Education, 2025)
One form of relevant religious value recognition is the introduction of halal labels on snacks frequently consumed by children. This study aims to describe the implementation of halal label recognition on everyday snacks for early childhood, including the implementation process, the role of teachers, and children's responses to the activity. This study used a qualitative approach implemented at the Smart and Cheerful Early Childhood Education Center in Taluak Village, Pariaman City, with group B1 as research subjects in the 2025/2026 academic year. Data collection techniques were carried out through observation and documentation. The results showed that halal labels implemented through simple and fun activities can improve children's initial understanding of halal food. Teachers play an important role as facilitators and role models in forming these habits through consistent practice. This study concludes that introducing halal labels on snacks can be an effective strategy in instilling religious values ​​in early childhood.